Piracy, Imitation, and Optimal Copyright Policy. (5th December 2017) - Randolph Beard, T.; Ford, George S.; Sorek, Gilad; Spiwak, Lawrence J.
Abstract : This article presents a model of optimal copyright policy which incorporates several realistic features which have hitherto been largely ignored. First, although copyright is understood as a means of encouraging the creation of new works, the optimal number of such works is generally not considered. Second, copyright infringement encompasses two different activities subsumed under the same legal umbrella: One might either "pirate" (i.e., illegally copy) a work or one might create a "new" work which is a close imitation of an existing one. The mutual recognition of these two features leads to some surprising conclusions relevant to current debate over copyright reform. In particular, while strong piracy protection encourages overproduction of intellectual property, enhanced protection against imitation can mitigate the associated inefficiencies, benefitting society.